2017
DOI: 10.1371/journal.pone.0178487
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age and weaning conditions on blood indicators of oxidative status in pigs

Abstract: Weaning is a source of social, nutritional and environmental disorders that challenge piglet health. This study assesses the relevance of using plasma indicators of oxidative status as biomarkers of health around weaning in pigs. Blood antioxidant potential (BAP), hydroperoxides (HPO), oxidative stress index (OSI, e.g. HPO/BAP), vitamin A and E concentrations were investigated in two different trials. Trial A was carried out in an experimental unit to investigate the effects of age (from 12 to 147 days of age)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
62
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(71 citation statements)
references
References 42 publications
7
62
0
2
Order By: Relevance
“…Several authors reported that peroxidized oil reduced serum concentrations of vitamin E due to catabolism of the vitamin E during oxidative stress [8,9,17,37,45]. This fact agrees with the results found in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Several authors reported that peroxidized oil reduced serum concentrations of vitamin E due to catabolism of the vitamin E during oxidative stress [8,9,17,37,45]. This fact agrees with the results found in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…The antioxidant potential was rather reduced when approaching the end of the weaning transition. These observations seem to correlate to our earlier observations at similar time points [44], whereas other studies reported either unaffected [46,47] or decreased [22,24,25,45,48] total antioxidant capacities in the first 2 weeks post-weaning. Yet, interesting evidence is provided by measurements of the GPx activity, as this was clearly increased in plasma and intestinal mucosa on d5-post-weaning.…”
Section: Discussionsupporting
confidence: 91%
“…Results clearly indicated that intestinal dysfunction after weaning is associated with unbalanced antioxidant systems as indicated by reduced super oxide dismutase (SOD), glutathione peroxidase (GPX) and increased ROS in the intestines and the blood. There is much interest in the use of assessing antioxidant status (Buchet et al, 2017) and compounds (Zhu et al, 2012) to mitigate this problem of antioxidant imbalance. Dietary polyphenols have been shown to play important roles in human health by lowering risks of many chronic diseases including cancer, cardiovascular disease, chronic inflammation and many degenerative diseases (Milner, 1994).…”
Section: Antioxidant Nutritionmentioning
confidence: 99%